(untitled) (The Peerian Journal, 2023)
This work is dedicated to the work of the famous Iranian writer - prose writer Bozorg Alavi, "Varaghe parehaye zendan" (Prison notes). The article also describes the life of prisoners, a description of the Iranian prison during the reign of Reza Shah. This work is devoted to the theme of prison in the works of Bozorg Alavi. The focus of consideration is the life of the prisoners of the Iranian prison in the 20th century